2009
DOI: 10.1007/s10162-009-0192-9
|View full text |Cite|
|
Sign up to set email alerts
|

Tympanic Membrane Boundary Deformations Derived from Static Displacements Observed with Computerized Tomography in Human and Gerbil

Abstract: The middle ear is too complex a system for its function to be fully understood with simple descriptive models. Realistic mathematical models must be used in which structural elements are represented by geometrically correct three-dimensional (3D) models with correct physical parameters and boundary conditions. In the past, the choice of boundary conditions could not be based on experimental evidence as no clear-cut data were available. We have, therefore, studied the deformation of the tympanic membrane (TM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…The ratio of displacements at positive/negative pressures was computed at approximately 1.8 which is in good agreement with experimental observations in human temporal bones with a ratio ranging between 1.8 and 1.9 [Hüttenbrink, 1988;Dirckx and Decraemer, 1991;Gea et al, 2010]. The mean ratio remained unchanged after the suppression of cochlea, stapes and stapedial tendon, while rigidifying the annular ligament influenced the umbo displacement below -200 daPa.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The ratio of displacements at positive/negative pressures was computed at approximately 1.8 which is in good agreement with experimental observations in human temporal bones with a ratio ranging between 1.8 and 1.9 [Hüttenbrink, 1988;Dirckx and Decraemer, 1991;Gea et al, 2010]. The mean ratio remained unchanged after the suppression of cochlea, stapes and stapedial tendon, while rigidifying the annular ligament influenced the umbo displacement below -200 daPa.…”
Section: Discussionsupporting
confidence: 73%
“…This observation suggests that the cochlea participates in the transfer function for high frequencies between 2,000 and 8,000 Hz. Figure 6 compares our model to previously published data in temporal bone specimens [Hüttenbrink, 1988;Dirckx and Decraemer, 1991;Gea et al, 2010] and to another FEM calculation [Wang et al, 2007]. The measured umbo displacement in our model was in good agreement with the experimental data.…”
Section: Transfer Functionsupporting
confidence: 74%
See 1 more Smart Citation
“…Gea et al (2010) found in their work on boundary deformations of the tympanic membrane a simply supported boundary condition for the pars flaccida at the bony edge. However, at the crease between the pars flaccida and the pars tensa, they found that the boundary was not perfectly fixed.…”
Section: Pars Flaccida Boundary Conditionsmentioning
confidence: 98%
“…In the literature, the TMC has been assigned different names, including manubrial fold Ferrazzini, 2003), stria 50 mallearis (Hoffstetter et al, 2010), plica mallearis (Gea and Decraemer, 2010;Gulya and Schuknecht, 1995) or simply TM-malleus attachment (Koike et al, 2002). Multiple studies have attempted to investigate the functional role of the TMC through finite element modeling, yet their conclusions are not aligned.…”
Section: Introductionmentioning
confidence: 96%